Description of a female and variation of Microgomphus alani Kosterin, 2016 (Odonata: Gomphidae) in Cambodia, with a note on sexual dimorphism in Microgomphus spp. - Kosterin, Oleg E. (Zootaxa, 2019)
Microgomphus alani Kosterin, 2016 was described from two teneral males from the Cardamom Mts. in SW Cambodia; it turned out that the description was based on the holotype with the anal appendages not fully expanded. Further specimens of M. alani (all mature) are reported: a male and two females from the Phnom Kulen Mts, NW Cambodia and five males and one female from Mondulkiri Province, E Cambodia. The appendage shape in mature males is illustrated and discussed and the female is described for the first time. The specimens from E Cambodia are ca 15-20% larger than those from SW and NW Cambodia and exhibit some differences in the shapes of the male epiproct and anterior hamulus and face maculation, however evaluated as insufficient to erect a new taxon. A hitherto neglected manifestation of sexual dimorphism in probably most Microgomphus spp. and at least some Heliogomphus spp. is pointed out. It concerns the mid- and metafemur, in males armed with numerous, dense and small spinulets but with two rows of long, sparse spines in females. An earlier report of Microgomphus jurzitzai Karube, 2000 for Cambodia was based on a misidentified M. alani specimen and is cancelled. A female specimen earlier identified and described from Thailand as Heliogomphus selysi Fraser, 1925 most probably was M. alani as well.